CDKL2 Is Associated with HER2 Status and Overall Survival in Gastric Cancer: Comparative Analysis of CDKL2 Protein Expression and Gene Copy Number. (31st October 2020) - Shao, Qiong; Wang, Fang; Xu, Yuxia; Zhang, Xu; Tang, Wenting; Feng, Yanfen; Li, Yue
Abstract : Background . Cyclin-dependent kinase-like 2 (CDKL2) is a member of the CDKL family and recognized as a novel regulator of epithelial-mesenchymal transition of breast cancer cells, but its role has not been explored in gastric cancer (GC). This study was to characterize the CDKL2 protein expression and gene copy number in relation to human epidermal growth factor receptor 2 (HER2) status, clinicopathological features, and overall survival (OS) in GC. Methods . This study detected the CDKL2 protein expression and gene copy number by immunochemistry (IHC) and fluorescent in situ hybridization (FISH), respectively, in 334 GC samples. HER2 status was determined according to established criteria. Associations of the CDKL2 protein expression and gene copy number with OS in GC were evaluated, and the association between CDKL2 mRNA expression and OS in GC was also analyzed using TCGA data. Results . The detection results suggested that 34.1% cases showed high CDKL2 protein expression; 11.4% cases had ≥5 copies of CDKL2 gene or a ratio of CDKL2 to chromosome of ≥2. The CDKL2 protein expression was markedly correlated with its gene copy number. High protein expression and high gene copy number were both significantly associated with positive HER2 status, and they both could predicted a shorter OS, although not as independent markers suggested by the multivariate Cox proportional hazard regression analysis. The TCGA data indicated that higher CDKL2 mRNA level also predicted a shorter OS in GC. Conclusions . The combined detection of the CDKL2 protein level and gene copy number could be of important value in predicting HER2 status and prognosis of patients with GC.